Chronic Unilateral Hearing Loss Disrupts Neural Tuning to Sound-Source Azimuth in the Rat Primary Auditory Cortex - Wang, Xiuwen; Liu, Jing; Zhang, Jiping (Frontiers in Neuroscience, 2019)
Accurate sound localization requires normal binaural input and precise auditory neuronal representation of sound spatial locations. Previous studies showed that unilateral hearing loss profoundly impaired the sound localization abilities. However, the underlying neural mechanism is not fully understood. Here we investigated how chronic unilateral conductive hearing loss (UCHL) affected the neural tuning to sound source azimuth in the primary auditory cortex (AI). The UCHL was manipulated by the removal of tympanic membrane and malleus in the right ear of young (P14) rats and adult (P57) rats. We recorded the azimuth tuning of neurons in the left AI contralateral to the operated ear in the two groups of rats that experienced two months of UCHL, and in the left AI of age-matched control rats. We found that AI neurons in control rats showed predominant preference to sound from contralateral azimuths. However, UCHL weakened the cortical neuronal representation of contralateral azimuths on the operated ear side and strengthened the cortical neuronal representation of ipsilateral azimuths on the intact ear side. This effect was stronger in rats with UCHL at young age than in rats with UCHL in adulthood. Moreover, UCHL degraded the azimuth selectivity and azimuth sensitivity of AI neurons, and this effect was stronger in rats with UCHL in adulthood than in rats with UCHL at young age. These findings highlight a remarkable age-related experience-dependent plasticity of neural tuning to sound source azimuth in AI, and imply a neural mechanism for the impacts of chronic UCHL on sound localization abilities.